Pengaruh Kinerja Keuangan, Leverage dan Pergantian Manajemen Terhadap Auditor Switching - Ardita, Akwine Jeny; Ricky, Ricky (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the effect of financial performance variables, leverage, and management turnover on auditor switching in food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. The population in this study consisted of 83 companies, and the final sample was 52 companies selected through purposive sampling, resulting in a total of 260 observations. Data analysis was conducted by applying binary logistic regression using SPSS. The dependent variable, auditor switching, was measured using a dummy variable, with companies that changed auditors given a value of 1 and companies that did not change auditors given a value of 0. Financial performance, as measured by ROA, did not have a significant effect on auditor switching. This may indicate that a decline in financial performance is not always the main driver for companies to change auditors, as other factors may be more dominant. Similarly, leverage had no significant effect on auditor switching. This study shows that the leverage variable, which serves as an indicator of a company's debt burden, also had no significant effect on the decision to change auditors. However, management turnover measured using dummy variables was found to have a significant and positive effect on auditor switching. These findings illustrate that the replacement of the chief executive officer or top management is the main factor driving companies to change auditors. This study is projected to provide comprehensive insights into the dynamics and factors that empirically influence auditor switching, particularly in food and beverage companies listed on the IDX.